(untitled) (Journal of Science and Technology Research, 2024)
Nutritionists are beginning to pay attention to black soldier fly (Hermetia illucens L.) larvae (BSFL) as an alternative to expensive soybean and fish meal in animal feed which is abundant in different nutrients. Additionally, organic wastes including leftover food, animal excreta, and agricultural wastes, can be used to efficiently raise and spread BSFL. This study was carried out to evaluate the yield, production performance and proximate composition of BSFL nurtured on different organic waste namely, broiler starter feed (BF); rice bran (RB); market-sourced vegetable wastes (VW); chicken manure (CM) and kitchen waste (KW). The BF fed group had the highest observed larval yields (16.2 kg in total; P<0.05). Raising BSFL on BF, VW and KW resulted in the greatest body weight (0.149, 0.147 and 0.150 g, respectively) and growth rate (0.012 g), whereas the KW fed group had the longest body length (P<0.05). The fed groups that received CM and BF had the highest and lowest mortality rates, respectively (P<0.05). All fed groups except RB had improved feed conversion ratios, while VW and KW fed groups had higher protein conversion ratios (2.626 and 2.852, respectively; P<0.05). All the group had better substrate reduction rate compared to CM fed group (P<0.05). The dry matter and ash contents of BSFL reared on BF, VW and KW were higher than the RB and CM group (P<0.05). The KW supplemented BSFL had the highest ether extract level, whereas the BF fed group had the highest protein content (43.58%, P<0.05). In conclusion, BSFL can be successfully reared on kitchen and vegetable scraps. It is anticipated that the cost of black soldier fly farming and animal production will decrease since these organic waste shown favorable effects on BSFL growth performance and nutritional quality comparable to broiler feed in the current study. J. of Sci. and Tech. Res. 6(1): 139-148, 2024